2020
DOI: 10.1016/j.jadohealth.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Distancing Policies During the COVID-19 Pandemic on Health and Well-Being Among Australian Adolescents

Abstract: Purpose Physical distancing policies in the state of New South Wales (Australia) were implemented on March 23, 2020, because of the COVID-19 pandemic. This study investigated changes in physical activity, dietary behaviors, and well-being during the early period of this policy. Methods A cohort of young people aged 13–19 years from Sydney (N = 582) were prospectively followed for 22 weeks (November 18, 2019, to April 19, 2020). Daily, weekly, and monthly trajectories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
238
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(276 citation statements)
references
References 15 publications
26
238
1
11
Order By: Relevance
“…Similar to many studies [ 1 , 2 , 19 ], we found a significant reduction in physical activities in the local population during the pandemic. Since the start of the community outbreak, the Hong Kong government has closed all sports centers and venues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to many studies [ 1 , 2 , 19 ], we found a significant reduction in physical activities in the local population during the pandemic. Since the start of the community outbreak, the Hong Kong government has closed all sports centers and venues.…”
Section: Discussionsupporting
confidence: 91%
“…While some studies indicated that eating patterns in various populations were unhealthier during the COVID-19 pandemic [ 16 ], we found that Hong Kong people increased their consumption of fruits and vegetables. The increased intake of healthy foods has seldom been reported in previous publications, with some exceptions in India [ 18 ], Thailand [ 2 ], and Australia [ 19 ], which found a decreased consumption of junk foods. As Hong Kong people have a fast pace of life, the adult population who tends to consume more food prepared in advance to save time, in particular, might be less aware of the nutritional information of their food and beverages, including cholesterol content [ 20 ].…”
Section: Discussionmentioning
confidence: 88%
“…Of the six studies that examined PA changes in healthy children and adolescents, all were measured using subjective questionnaires, with half using validated questionnaires. Two studies 48 84 used total scores from validated questionnaires and two studies 65 82 reported PA changes in the form of a time measurement, all reporting decreases in PA. Two studies 62 71 reported PA changes as a percentage of the respective population and reported >50% of the population decreased their PA during lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…As educational centers were closed, social contacts became greatly limited, and leisure time activities were canceled (Fegert et al, 2020). Measures implemented in the field of physical distancing resulting from the COVID-19 virus have been associated with a decrease in physical activity and well-being, an increase in loneliness and Internet use among adolescents (Munasinghe et al, 2020). Among the mental health problems related to quarantine, we find depression, mood swings, anger, insomnia and emotional exhaustion (Brooks et al, 2020).…”
Section: Introductionmentioning
confidence: 92%